An Analysis of Students’ Writing Skill on English Descriptive Text - Purnamasari, Dewi; Hidayat, Didin Nuruddin; Kurniawati, Lia (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study analyzed the writing skills in English descriptive text. There are five indicators in writing descriptive text: content, organisation, grammar, vocabulary, and mechanics. Therefore, this study aimed to investigate the students' writing skill on descriptive text related to the five indicators of English descriptive text and investigated the difficulties in writing English descriptive text. This research study used a descriptive quantitative research design. The participants were eighth-grade students at SMPN 16 South Tangerang. The data gained from students' writing descriptive text test and analyzed by using Heaton’s theory. The result showed that: 1) 43% of students obtained scores ranging from average to good in writing content, 2) 44% of students obtained scores ranging from average to good in writing organization, 3) 37% of students obtained scores ranging from average to good in using grammar, 4) 33% of students obtained scores ranging from very good to excellent in using vocabulary, 5) 27% of students obtained scores ranging from very good to excellent in writing mechanics. Further, the study found some difficulties the students face when writing descriptive. First, students cannot develop their ideas. Second, the students have insufficient knowledge about the subject that will be described. Third, the students have difficulties in using a simple present tense.